Risk assessment of maternally inherited SDHD paraganglioma and phaeochromocytoma. Issue 2 (17th November 2016) - Burnichon, Nelly; Mazzella, Jean-Michaël; Drui, Delphine; Amar, Laurence; Bertherat, Jérôme; Coupier, Isabelle; Delemer, Brigitte; Guilhem, Isabelle; Herman, Philippe; Kerlan, Véronique; Tabarin, Antoine; Wion, Nelly; et al.
Abstract : Background: Germline mutations in the SDHD tumour suppressor gene (11q23.1) predispose to phaeochromocytomas and paragangliomas (PPGL) mainly on a paternal transmission. However, PPGL have been recently reported in three carriers of a maternally inherited SDHD mutation. Objective: To assess the risk of PPGL occurrence on maternal transmission of SDHD mutation. Methods: Pedigrees of 80 SDHD -related families have been reviewed. 35 asymptomatic subjects carrying a maternally transmitted SDHD mutation were identified. 20 of them accepted to benefit from a PPGL imaging screening. Results: A unique histologically proven biochemically negative phaeochromocytoma has been diagnosed in a 35-year-old woman. Molecular investigations carried out on tumour tissue revealed that the loss of heterozygosity encompassed the paternally derived q arm and the maternally derived p arm of chromosome 11. Conclusions: This study demonstrates that the risk of developing PPGL for a subject carrying a germline SDHD mutation on the maternal allele remains a rare scenario but does exist. Our data suggest an adjustment of current genetic counselling and clinical care recommendations for at-risk subjects. A targeted familial genetic test should be proposed from the age of 18 years to every subject having a mother carrying a germline SDHD mutation and a first medical workup, including imaging, should be recommended to SDHD -positive mutation carriers.